Students’ and Lecturers’ Perceptions of Euphemism Use in Everyday and Academic Communication - Erna Andriyanti; Purwaningtyas Dwi Astuti; Susana Widyastuti; Paulus Kurnianta (k@ta: A Biannual Publication on the Study of Language and Literature, 2026)
Euphemism is used to manage potentially sensitive language and interpersonal relationships. However, limited research has examined how students and lecturers perceive its use across everyday and academic communication. To address this gap, this mixed-methods study examined students’ and lecturers’ perceptions of euphemism use, including its reported forms and perceived functions, across these two settings. Data were collected through an online questionnaire completed by 96 students from five universities in Yogyakarta and 26 lecturers from ten universities in and outside Yogyakarta. Both groups regarded euphemism as a necessary part of communication. In everyday communication, it was mainly associated with avoiding vulgar, taboo, socially unacceptable, embarrassing, or potentially hurtful expressions. Students more frequently associated euphemism with avoiding awkward situations, whereas lecturers more frequently associated it with empathy and sensitivity. In academic communication, particularly classroom interaction, euphemism was more strongly associated with mutual respect and a supportive, non-threatening environment; few participants linked it with softening correction. The findings highlight the importance of balancing tactful wording with clarity across everyday and academic communication.